Future Fetch: Towards a ticket-based data access for secondary storage in database systems - Vöhringer, Demian; Meyer-Wegener, Klaus (Proceedings of the Conference "Lernen, Wissen, Daten, Analysen", 2020)
When accessing data from a database, a database management system has to accomplish many tasks. Checking the conformity of the query, generating a reasonably good query plan and executing it in a concurrent system are just a few of them. During query execution, there are some points at which the main execution thread must stop and wait for data. This synchronous waiting can have a major impact on the overall query performance. In this paper we introduce the idea of a ticket-based fetch, which supports the database management system by waiting for data asynchronously. This can improve the query-execution performance in database systems.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Asynchronism; Big Data; Concurrent; Data Access; Data Flow; Data Warehouse; Database System; Ticket

Query-Driven Enforcement of Rule-Based Policies for Data-Privacy Compliance - Schwab, Peter; Langohr, Maximilian; Röckl, Jonas; Vöhringer, Demian; Wahl, Andreas Maximilian; Meyer-Wegener, Klaus (Proc. Conf. "Lernen, Wissen, Daten, Analysen", 2019)
Keywords: Classification Rules; Data Privacy; Query-Driven

Write-Aware Timestamp Tracking: Effective and Efficient Page Replacement for Modern Hardware - Vöhringer, Demian; Leis, Viktor (Proceedings of the VLDB Endowment, 2023)
In this paper, we revisit the classical data management problem of page replacement. We propose Write-Aware Timestamp Tracking (WATT), a novel replacement algorithm that is optimized for modern hardware. By explicitly tracking the access history of each cached page, WATT achieves state-of-the-art replacement effectiveness. WATT is also carefully co-designed with modern multi-core CPUs and can be implemented with very low overhead. Finally, WATT allows trading of read versus write I/O operations, which is useful for prolonging flash SSD lifetime.
Keywords: WATT; Write Aware Timestamp Tracking; Page Replacement; RAM; Database; LRU